2013
DOI: 10.1111/imm.12164
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis infection of human dendritic cells decreases integrin expression, adhesion and migration to chemokines

Abstract: SummaryTuberculosis (TB) remains a major global health problem accounting for millions of deaths annually. Approximately one-third of the world's population is infected with the causative agent Mycobacterium tuberculosis. The onset of an adaptive immune response to M. tuberculosis is delayed compared with other microbial infections. This delay permits bacterial growth and dissemination. The precise mechanism(s) responsible for this delay have remained obscure. T-cell activation is preceded by dendritic cell (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 53 publications
4
30
0
2
Order By: Relevance
“…All other gene expression assays were performed with unlabelled forward and reverse primers described previously in a reaction similar to above with SsoFast™ Evagreen ® Supermix (Bio‐Rad). Unlabelled human GAPDH and CD18 primer sequences were described previously . All remaining primer sequences were as follows: CD80, 5′‐tgacatcagcagagaact‐3′ (forward); CD80, 5′‐gaattgtggaaggcagtt‐3′ (reverse); CD86, 5′‐ctcaagataatgtcacagaact‐3′ (forward); CD86, 5′‐agatggtcatattgctcgta‐3′ (reverse); HLA‐DR, 5′‐agcagtcatcttcagcat‐3′ (forward); HLA‐DR, 5′‐atgttagagtacggagcaat‐3′ (reverse); human IDO1, 5′‐agaggagcagactacaag‐3′ (forward); human IDO1, 5′‐agcccacttcttcatcaa‐3′ (reverse); ARG1, 5′‐gaacagtgaacacagcag‐3′ (forward); ARG1, 5′‐ttacttaggtgggttaaggt‐3′ (reverse).…”
Section: Methodsmentioning
confidence: 99%
“…All other gene expression assays were performed with unlabelled forward and reverse primers described previously in a reaction similar to above with SsoFast™ Evagreen ® Supermix (Bio‐Rad). Unlabelled human GAPDH and CD18 primer sequences were described previously . All remaining primer sequences were as follows: CD80, 5′‐tgacatcagcagagaact‐3′ (forward); CD80, 5′‐gaattgtggaaggcagtt‐3′ (reverse); CD86, 5′‐ctcaagataatgtcacagaact‐3′ (forward); CD86, 5′‐agatggtcatattgctcgta‐3′ (reverse); HLA‐DR, 5′‐agcagtcatcttcagcat‐3′ (forward); HLA‐DR, 5′‐atgttagagtacggagcaat‐3′ (reverse); human IDO1, 5′‐agaggagcagactacaag‐3′ (forward); human IDO1, 5′‐agcccacttcttcatcaa‐3′ (reverse); ARG1, 5′‐gaacagtgaacacagcag‐3′ (forward); ARG1, 5′‐ttacttaggtgggttaaggt‐3′ (reverse).…”
Section: Methodsmentioning
confidence: 99%
“…Dendritic cells were harvested and phenotypic analysis was performed as previously described . Briefly, DCs were suspended in 0·1 ml of staining buffer (0·5% BSA in PBS) and Fc receptor was blocked for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…Transmigration of dendritic cells through the endothelium is required to reach lymph nodes for antigen presentation. Studies have shown that M. tuberculosis can regulate dendritic cells integrin expression and thereby inhibit their adherence and migration in response to chemokine stimulation 58 . Delayed migration of dendritic cells was associated with reduced M. tuberculosis Ag85B‐specific CD4 T‐cell proliferation and activation, 59 which favours M. tuberculosis growth.…”
Section: Endothelial Cellsmentioning
confidence: 99%